The return to SENA after 40 years. Reflections on SENA 20 years later - Vargas Zúñiga, Fernando
This is a narrative about the results of vocational training, which refers to how I lived this experience and how I felt the pedagogy, how it promoted my career and how it has been an incomparable motor of mobility and promotion in my life. I was linked to SENA for 20 years, one of them as a student, three months in an internship and the rest of time as an official. I detached myself from the entity as an official 20 years ago, but due to my work, I follow closely its mission, challenges, and achievements. Surely this is a repeated story for many, perhaps it will sound new to others; but among the millions of people who every day have the opportunity to access a source of knowledge and skills, perhaps some readers will find issues of reflection and, why not, of dissent.